1997
DOI: 10.1016/s1078-5884(97)80102-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of treadmill tests and heel raising exercise for peripheral arterial disease

Abstract: Heel raising produced changes in ankle pressure which correlated well with those induced by treadmill exercise. We recommend the use of simple heel raising when a stress test is required to diagnose lower limb arterial insufficiency in the outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Potential participants with an ABI >0.90 are also eligible, if a certified vascular laboratory demonstrated prior lower extremity ischemia. Participants with prior lower extremity revascularization are eligible only if they have a 20% drop in ABI following a heel-rise test (27). Based on our experience in prior clinical trials of participants with PAD, fewer than five percent of all participants will be included because they have an ABI > 0.90 at baseline and meet one of these criteria (28).…”
Section: Methodsmentioning
confidence: 99%
“…Potential participants with an ABI >0.90 are also eligible, if a certified vascular laboratory demonstrated prior lower extremity ischemia. Participants with prior lower extremity revascularization are eligible only if they have a 20% drop in ABI following a heel-rise test (27). Based on our experience in prior clinical trials of participants with PAD, fewer than five percent of all participants will be included because they have an ABI > 0.90 at baseline and meet one of these criteria (28).…”
Section: Methodsmentioning
confidence: 99%
“…Potential participants with a resting ABI ≥ 0.91 and ≤ 1.00 at baseline are eligible if their ABI drops by at least 20% following a heel-rise test (18,19). Prior study shows that an ABI decline > 20% after the heel-rise test is highly correlated with ABI declines after a treadmill exercise stress test (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…Potential participants with a resting ABI ≥ 0.91 and ≤ 1.00 at baseline are eligible if their ABI drops by at least 20% following a heel-rise test (18,19). Prior study shows that an ABI decline > 20% after the heel-rise test is highly correlated with ABI declines after a treadmill exercise stress test (18,19). Potential participants with a resting ABI greater than 0.90 are also potentially eligible if they provide data from a certified vascular laboratory demonstrating prior lower extremity ischemia or if they have medical record documented evidence of prior lower extremity revascularization.…”
Section: Methodsmentioning
confidence: 99%
“…Thus the Naughton protocol may represent a more precise and reproducible exercise test, and previous studies have shown that the Naughton test appears to be a more sensitive measure in detecting changes in exercise capacity compared with the 6-min walking test in less sick patients with PH [36]. However, some elderly patients find treadmill assessments stressful or perform poorly due to restricting factors in more severe cardiovascular co-morbidities [37]. The use of the Naughton test can be problematic, as the test is terminated when the patient is unable to maintain the imposed workload.…”
Section: Figure 2 Distribution Of Urinary Et-1 At Baseline and Duringmentioning
confidence: 99%